Application of Water Hyacinth Liquid Bio-Organic Fertilizer Using Trichoderma Sp Bio-activator on Growth and Production of Green Mustard Plants (Brassica rapa var. Parachinensis) - Febiayu Aloatuan; Centhya Victorin Maitimu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2020)
Mustard greens (Brassica rapa var. Parachinensis) are known vegetables among consumers and have high economic value. Besides being used as a vegetable, mustard greens are also used for the treatment of various diseases so that they are included in the vegetable group which has an important role in meeting the needs of food, nutrition and medicine for the community. To increase the growth and production of green mustard plants, it is necessary to apply liquid bio-organic fertilizers that are sourced from organic materials with good nutrients needed by plants, one of which is water hyacinth weed. To improve the quality of water hyacinth liquid bio-organic fertilizer, it can be applied with the bio-activator Trichoderma sp which functions to produce liquid bio-organic fertilizer with high nutrients for plant growth and production. The purpose of this study was to determine the growth of mustard greens including plant height, number of leaves and leaf width and to test the production of mustard greens including caratenoids and vitamin C content. This study used a completely randomized design (CRD) with a single factor, namely fertilizer. Liquid organic (POC) water hyacinth fermented using Trichoderma sp. which consists of 5 levels of fertilization doses, namely A (0 ml / L), B (8 ml / L), C (16 ml / L), D (24 ml/L) and E (32 ml/L) with 5 repetitions. Based on the results of analysis of variance, it showed that the dosage treatment of water hyacinth bio-organic fertilizer with the bio-activator Trichoderma sp had a significant effect on p <0.05 on plant height, leaf width and the number of green mustard leaves at 4 weeks of age 21 day after planting. with the results of the chemical content test which showed that treatment E (32 ml/L) contained Karetenoid (0,2596 mg/100g of material) and vitamin C (0.2784 mg/100 g of material). The best dose based on the results of the study was treatment E (32 ml/L) which had a higher average plant height, leaf width and number of leaves compared to other treatments and had high vitamin A and vitamin C content. To increase the growth and production of mustard greens and other horticultural cultivation processes, it is advisable to use liquid bio-organic fertilizer for water hyacinth with the bio-activator Thricoderma sp as an alternative to natural, environmentally friendly liquid organic fertilizer.